Investigating forward velocity and symmetry in freestyle swimming using inertial sensors - Stamm, A.; Thiel, D. V. (Procedia Engineering, 2015)
Investigating the performance of an athlete and monitoring them is important to athletes and coaches because it can provide information about the training progress and injury recovery. Coaches are not always on side when athletes doing their training, so a device which is small and easy to use will increase the monitored training sessions significantly and allow the athlete to compare multiple training sessions. This technology has seen rapid development over the last years and is now available in very small sizes which have little effect on the swimmer. Using this kind of sensor, kinematics can be measured and extracted for stroke characteristics investigations. This research used an sacrum mounted self-developed inertial sensor, providing a triaxial accelerometer, gyroscope and RF capability in a waterproof casing to investigate the arm symmetry and swimming velocity in freestyle swimming. The recorded data were filtered using a high-pass Hamming windowed FIR filter to remove the gravity components from the wanted signal. The acceleration signal was then processed to find the velocity of the swimmer. A zero-crossing detection algorithm was used to investigate the arm symmetry and to find the individual stroke rates (SR), the differences between left and right arm stroke durations and the left and right arm stroke velocities (asymmetry). The investigation of the left and right arm velocity patterns of each individual swimmer allowed the investigation of each swimmers asymmetry in propulsion and velocity for the individual arms. The results of the mean lap velocities showed that the two different methods agree with an R^2 of 0.92. Furthermore a conducted Bland-Altman analysis showed a low bias of -0.04 with an upper limit of agreement of 0.03 and a lower limit of agreement of -0.11.